1997
DOI: 10.1002/(sici)1099-1085(199707)11:9<1231::aid-hyp554>3.0.co;2-a
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal modelling of catchment water balance: A two-levle cascading modification of TOPMODEL to increase the realism of spatio-temporal processes

Abstract: A general problem of hydrological modelling is parameter identi®cation for the driving processes. To examine the longterm dynamics of the water balance of a small (4 . 2 km 2 ) forested catchment in south-east Germany (Lehstenbach), TOPMODEL has been adapted as a two-level cascading approach. Only the lower cascade is allowed to respond dynamically. This modi®ed TOPMODEL version accounts for the observations that surface runo only takes place in a small portion of the catchment and that water¯ow in large porti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

1997
1997
2017
2017

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 19 publications
1
2
0
Order By: Relevance
“…The main message here is that there may be a number of dynamic behavior patterns in any catchment, which can be captured by a few key landscape elements. This is in agreement with the idea to delineate differently reacting regions in a catchment based on topographical indices [e.g., Ostendorf and Manderscheid , 1997] or with the hydrogeomorphic concept proposed by Sidle et al [2000], in which different components of a catchment are supposed to exhibit unique hydrologic behaviors. We propose that while the steady state assumption for entire hillslopes or catchments may be inappropriate, this does not rule out the value of applying this assumption to individual zones within a catchment.…”
Section: Discussionsupporting
confidence: 87%
“…The main message here is that there may be a number of dynamic behavior patterns in any catchment, which can be captured by a few key landscape elements. This is in agreement with the idea to delineate differently reacting regions in a catchment based on topographical indices [e.g., Ostendorf and Manderscheid , 1997] or with the hydrogeomorphic concept proposed by Sidle et al [2000], in which different components of a catchment are supposed to exhibit unique hydrologic behaviors. We propose that while the steady state assumption for entire hillslopes or catchments may be inappropriate, this does not rule out the value of applying this assumption to individual zones within a catchment.…”
Section: Discussionsupporting
confidence: 87%
“…In general, TOPMODEL assumptions appear to hold in humid catchments with rolling topography. Several studies (Barling et al, 1993;Ostendorf and Manderscheid, 1997;Woods et al, 1997) have found that the assumption of steady state flux is violated during drier periods. In drier periods, areas of the catchment may become disconnected and thus the extent of effective contributing areas becomes more local.…”
Section: Topmodel (Implicit Routing)mentioning
confidence: 99%
“…In Beven and Kirkby's TOPMODEL (1979), the watershed's topography is the major factor in the generation and control of the runoff, with surface flow occurring only in those parts of the watershed where saturation is reached. From this model's basis, many variations have been described to add or change some of the processes involved (Band et al, 1993;Troch et al, 1994;Ambroise et al, 1996a;Ambroise et al, 1996b;Beven, 1997;Iorgulescu and Musy, 1997;Ostendorf and Manderscheid, 1997;Piñol et al, 1997;Saulnier et al, 1997;Woods et al, 1997;Lane et al, 2004;Niu et al, 2005;Wang et al, 2005Wang et al, , 2006Llorens et al, 2006;Wu et al, 2006;Chen et al, 2007).…”
Section: Introductionmentioning
confidence: 99%